Enhancing Foreign Direct Investment via Transparency? Evaluating the Effects of the EITI on FDI - Maya Schmaljohann (University of Heidelberg, Department of Economics, 2013)
The so called resource curse, the fact that countries rich in natural resources often show lower rates of economic growth compared to resource-poor countries, is commonly attributed to the low quality of governance in resource-rich countries. The Extractive Industries Transparency Initiative (EITI) was founded in 2003 to address this problem through increasing the quality of the public financial management of resource flows. By joining this initiative, governments show their willingness to reform and to improve their governance. As the quality of governance is an important factor for investors in deciding where to invest, this signal has the potential to improve a country's appeal for foreign direct investment (FDI). This study shows in a panel of 81 countries that joining the EITI increases the ratio of FDI inflows to GDP on average by around two percentage points. This is a remarkable increase given that the average ratio of FDI inflows to GDP in the sample is five percent. The results are robust when controlling for selection bias due to the voluntary decision to join the initiative and possible endogeneity of the candidate variable.
urn:nbn:de:bsz:16-heidok-143684
Keywords: 330; FDI; EITI; Corruption; Natural Resources